SISTEM PENGAMAN DOKUMEN MENGGUNAKAN FINGERPRINT DAN RFID MODUL BERBASIS ARDUINO - Mohamad Irkam (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
Documents are securities / important that can be used as evidence of information that is printed or written in nature. The company where the author conducts research is a company engaged in logistics, which certainly has a special document storage room, the Accounting room. The use of plastic folders containing documents and metal cupboards as a place to store important documents and files still has many risks of misuse and loss. The title of this research is the Document Security System Using the Arduino-Based Fingerprint and RFID Module. The purpose of this study is to minimize losses and prevent misuse of documents / files that are inserted into a plastic folder. The security system using Fingerprint and RFID is very good to be applied as a document security because it has multiple security. The system is made using the Fingerprint as a signal breaker or electromagnetic wave RFID Tag attached to the Map containing the documents / important files belonging to the company. This system is also supported by the ArduinoUno kit with the Atmega328 microcontroller as the brain to process data from fingerprint sensors and RFID Readers that function as electromagnetic wave identification systems on the RFID Tag, therefore two hardware devices called Tag and Reader are needed. Apart from the three main components mentioned, there are several other components used in the manufacture of this document security system, namely the micro SD kit, buzzer, push button, servo. Making this system is very important in order to limit the misuse of documents and the risk of losing documents in a company.